PENGARUH KEMAMPUAN KONEKSI MATEMATIS DAN GROWTH MINDSET TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Nabila, Tri; Hidayah, Nurina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematical problem-solving ability is an important competence in mathematics learning because students are required to understand problems, plan strategies, carry out solutions, and review the results obtained. However, this ability remains a challenge because students tend to experience difficulties in solving word problems or problems that require deeper understanding. This study aims to determine the effect of mathematical connection ability and growth mindset on students’ mathematical problem-solving ability. This study used a quantitative approach with an ex post facto method. The sample consisted of 33 tenth-grade students of SMA Negeri 1 Pekalongan selected using cluster random sampling. Data were collected through tests and a questionnaire. Data analysis was conducted using prerequisite tests, simple linear regression, and multiple linear regression. The results showed that mathematical connection ability had a positive effect on mathematical problem-solving ability with a contribution of 22.2%. Growth mindset also had a positive effect with a contribution of 47.3%. Simultaneously, mathematical connection ability and growth mindset had a positive effect on mathematical problem-solving ability with a contribution of 50.1%. Thus, mathematical connection ability and growth mindset are factors that support students’ mathematical problem-solving ability.